Trends in drug offers among adolescents in the United States, 2002-2014 - Sehun Oh; Christopher P. Salas-Wright; Michael G. Vaughn (BMC, 2017)
Abstract Background Being offered illicit drugs is a critical factor leading to drug initiation and other psychosocial risk behaviors among adolescents in the United States. However, there exist few studies examining the recent trends in drug offers among adolescents, particularly across racial/ethnic subgroups. The present study examines trends and psychosocial/behavioral correlates of drug offers among adolescents of the three largest racial/ethnic groups. Methods We used data from the 2002-2014 National Survey on Drug Use and Health of adolescents aged 12-17, which include African-American, Hispanic, and White adolescents (n = 199,700) in the U.S. We estimated the prevalence of past-month drug offers by race/ethnicity, and conducted logistic regression analyses to test the significance of the trends and to examine the correlates of drug offers. Results Overall, the prevalence of drug offers decreased significantly from 16.3% in 2002 to 12.3% in 2014, reflecting a 24.5% reduction in the relative proportion of adolescents who were offered drugs. While the decreasing trends were observed in all subgroups (e.g., race/ethnicity), the decreases were more limited among African-American and Hispanic youth than White youth. As a result, while no differences were observed at the outset of the study, a higher proportion of African-American and Hispanic adolescents were offered drugs between 2012 and 2014. Conclusions Findings suggest a general decline in drug offers among adolescents in the U.S., but racial/ethnic differences in prevalence were identified. This underscores the importance of further efforts to understand the racial/ethnic differences in drug offers and suggests the need for culturally-sensitive drug prevention programs.